2021
DOI: 10.1007/s12144-021-01985-0
|View full text |Cite
|
Sign up to set email alerts
|

Using the health action process approach to predict facemask use and hand washing in the early stages of the COVID-19 pandemic in China

Abstract: Personal hygiene including wearing facemask and washing hands are instrumental to reduce transmission of COVID-19. The present study applied the health action process approach (HAPA) to examine the process from intention to protective behaviors in the early stages of the COVID-19 pandemic. A longitudinal online survey study was conducted among 229 individuals (61.6% females; M age = 25.37 years, SD age = 8.34 years) living in Hubei provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
(52 reference statements)
5
19
1
Order By: Relevance
“…There is a growing number of studies attempting to explain handwashing behavior during the COVID-19 pandemic pointing towards the predicting role of various individual-level variables (e.g., social-cognitive or sociodemographic) [3,[7][8][9][10][11] and environmental-level factors (e.g., characteristics of the setting) [14]. However, these Participants were asked to indicate if during the previous week they have usually washed their hands (for at least 20 s, all surfaces of the hands) in the respective situation (with responses ranging from 1 = strongly disagree to 4 = strongly agree).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a growing number of studies attempting to explain handwashing behavior during the COVID-19 pandemic pointing towards the predicting role of various individual-level variables (e.g., social-cognitive or sociodemographic) [3,[7][8][9][10][11] and environmental-level factors (e.g., characteristics of the setting) [14]. However, these Participants were asked to indicate if during the previous week they have usually washed their hands (for at least 20 s, all surfaces of the hands) in the respective situation (with responses ranging from 1 = strongly disagree to 4 = strongly agree).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the underlying mechanisms through which COVID-19 morbidity and mortality trajectories may affect protective behavior were not investigated. Such mechanisms may include individuals' unconscious processes [25], or they may depend on changes in risk perception [30], risk awareness [7], knowledge about SARS-CoV-2 transmission [8], behavioral intention and action control [11], or other social cognitive variables [9,10,15]. Future research should investigate if pandemic trajectory variables explain protective behavior over and above a set of theory-based predictors of handwashing or can be fully explained by these psychological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some previous research indicates that outcome expectations are unrelated to the ability to change behaviour, it has been suggested that further validation be conducted because outcome expectations have varying effects across fields of study (Lao et al, 2021). Thus, this research proposes the following hypothesis:…”
Section: Outcome Expectancies and Preventive Behaviourmentioning
confidence: 90%